PERCEPTION OF OCCUPATIONAL STRESS BY MILITARY FIREFIGHTERS FROM A CITY IN THE COUNTRYSIDE OF MINAS GERAIS - Natália Gomes Vicente (Revista de Pesquisa Cuidado é Fundamental Online, 2013)
Objective : to identify the factors those predispose the military fireman to develop occupational stress. Method : this was a descriptive study, with quantitative and qualitative approach. 32 interviews were conducted using a semi - structured questionnaire an d an interview recorded with guiding questions. The data were analyzed using the SPSS 16.0 version and for the interviews was used content analysis. Results: Seven categories namely: understanding stress, stress in daily work; factors stressors and emotional damage due to stress. Conclusion: It was noticed in this study the difficulty of theoretical science on this subject. Moreover, we can infer that concern firefighters, feel and express stress in different ways and thus to realize when they are under job stress.